Challenges and Barriers of Online Teaching: Perspective of Faculty in a Private Medical College of Lahore - Naureen Omar; Ifra Aslam; Syeda Mahnoor Nadeem; Ramsha Batool; Umbreen Navied; Muhammad Subhan Feroze (Journal of University College of Medicine and Dentistry)
Objective: To identify the challenges and barriers faced during initiation of online teaching by the faculty of a private medical college of Lahore. Methodology: This cross-sectional study was conducted from Sep-Dec, 2021 in FMH College of Medicine and Dentistry, Lahore. List of faculty members was obtained from the Human Resource Department amounting to 140, a sample size of 70 was selected which was the half of total sample. A predesigned, structured questionnaire was used. Approval from IRB committee and consent was obtained. Data was collected online using Google Performa via email, analyzed using SPSS version 20 and Microsoft Excel. Percentages, proportions and means were calculated. Results: The respondents included 23 (32%) Demonstrators, 11 (15.7%) Senior Demonstrators, 22 (31.4%) Assistant Professors, 7 (10%) Associate Professors and 7 (10%) Professors. Year wise distribution of faculty was as follows; 13 (18.5%) were teaching 1st year, 9 (12.8%) 2nd year, 19 (27%) 3rd year, 25 (35 .7%) 4th year, and 4 (5.7%) final year MBBS respectively. Mean age in years was 39±9.8 of the enrolled faculty. Predominance of females 47 (67.1%) to males 23 (32.9%) was observed. Maintaining class decorum and controlling students' plagiarism was a major challenge for 65 participant s(92.9%). Inadequate online teaching resources were recognized by 61 (87.1%) to be a challenge making it difficult to inculcate clinical skills while, 58 (82.9%) accepted effectiveness of lecture was interfered by lack of face to face interaction. Most common barrier 60 (85.7%) was connectivity issues, software failure, power issues and 57(81.40) complained of lack of finances. Conclusion: Lack of face to face interaction, connectivity, software and power failure issues, in addition to finances and time management were major challenges and barriers faced during initiation of online teaching by the faculty.